On the masses and voters: people, democracy and political dispute 1950-1960 (Tempo e Argumento, 2021)
This article analyzes the transformations in the political languages of the 1950s in Brazil. More specifically, the speech acts related to democracy and the evaluations made on the extension of the vote, as well as in the relation to the country’s economic development. Editorials of national newspaper – Correio da Manhã, Tribuna da Imprensa, A Noite, Última Hora and Jornal do Brasil – were analyzed during the presidential campaigns of 1950, 1955 and 1960. The post-war period in Brazil was marked by the perspective of changing national structures. The perception of the need for social, economic and political changes was directly linked to a conception of temporality typical of these “euphoric years”. This scenario was marked by the democratization process in Brazil and the search for economic development. The concepts of democracy and development, in this sense, will be disputes on the pages of newspaper in the midst of the intense political context. The analysis is made from the contributions of the history of concepts and linguistic contextualism, understood in this article as complementary from a theoretical and methodological point of view